Improving Students' Critical Thinking Skills Through the ARCS Learning Model Assisted by Powtoon Media in Grade V Science Lessons at SDN 2 Tapa Bone Bolango - Sonia (Journal of Education and Teaching Learning, 2026)
This research is a Classroom Action Research (CAR) with the formulation of the problem is whether the application of the ARCS (Attention, Relevance, Confidence, Satisfaction) learning model assisted by PowToon media can improve students' critical thinking skills in the science subject on ecosystem material in grade V SDN 2 Tapa Bone Bolango. The purpose of this study is to improve students' critical thinking skills through the application of the ARCS learning model assisted by PowToon media. This research was conducted in two cycles, where each cycle consisted of two meetings with four stages: planning, implementation of actions, observation, and reflection. The research subjects were 18 students consisting of 13 male students and 5 female students. The results of the study showed that in cycle I of 18 students only 3 students achieved the Minimum Completeness Criteria (KKM ≥ 80) with a percentage of 16.67%, while 15 students or 83.33% had not achieved completeness. After improvements were made to the learning process in Cycle II, students' critical thinking skills significantly improved, with 16 students (88.89%) achieving mastery, while 2 students (11.11%) had not. Therefore, it can be concluded that the ARCS learning model, supported by PowToon media, can improve students' critical thinking skills in the fifth-grade science subject of ecosystem at SDN 2 Tapa Bone Bolango.